Do Local Governments Tax Homeowner Communities Differently? - Oliver Lerbs; Roland Füss (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Using data from a complete housing inventory in the 2011 German Census and historical war damages as a source of exogenous variation in local homeownership, we provide evidence that otherwise identical jurisdictions charge lower property taxes when the share of homeowners in their population is higher. The result is independent of local market conditions, suggesting tax salience as key mechanism. We find positive spatial dependence in tax multipliers, indicative of property tax mimicking.
Keywords: D72; H20; H71; H72; H77; 330